Evidencia experimental da existencia de uma linha multicritica de lifshitz no diagrama de fase MNp. - Brumatto, Hamilton Jose (1990)
Experimentally pure Lifshitz critical behavior has only been reported in the orthorhombic magnetic system MnP which exhibits uniaxial Ising-Type Lifshitz points LP (d=3, n=l, m=l). Two LPs have been previously identified in MnP. One when the external magnetic field H was applied along the intermediate b axis, the other when IH was along the hard anisotropy axis a. Both LPs occurs roughly at the same temperature (TL ~121K) but at different values of H due to the difference in anisotropy. In this work we report on measurements made with H applied within the ab plane. Two configurations were studied: (1) with H making an angle of 20° with the b axis and (2) with H at 45° in the b (and a) axis. The observed phase diagram obtained using an AC susceptibility technique shows, near the confluence of the modulated and ferromagnetic phases with the paramagnetic phase, the same characteristics of the phase boundaries found when H is along a and also along b . The temperature at the multicritical point is TL~120K. From an analysis of the shape of the phase boundaries near TL we obtained a crossover exponent =0.61±0.02, a value that is consistent with the found for IH along the a and the b axis. This value is also consistent with the predicted theoretically from Renormalization-Group calculation. These data suggest that there is a line of LPs connecting the multicritical points found when H is along the b and a axis.